Implementing Health Maintenance Guarantee Programs in Rural Primary Healthcare: A Case Study of Community Health Centers in Eastern Indonesia - Hukul, Wiwin; Selanno, Hendry; Waisapy, Jeanly (PUBLICUS: Jurnal Administrasi Publik, 2026)
The Health Maintenance Guarantee Program plays a crucial role in ensuring equitable access to healthcare services, particularly for underserved rural communities. This study aims to analyze the implementation of the Health Maintenance Guarantee Program at a rural community health center in Eastern Indonesia. Using a qualitative case study approach, the research explores how policy objectives are translated into practical healthcare services at the grassroots level. Data were collected through in-depth interviews with healthcare workers, direct observations, and document analysis involving program implementers and community representatives. The analytical framework is based on Edward III’s policy implementation model, which emphasizes communication, resources, disposition of implementers, and bureaucratic structure. The findings reveal that the implementation of the Health Maintenance Guarantee Program has generally improved access to basic healthcare services for low-income populations. However, several challenges persist, including limited medical facilities, inadequate human resources, and insufficient support from local government authorities. Communication between policy implementers and beneficiaries remains suboptimal, affecting public understanding of service entitlements under the program. Despite these constraints, healthcare workers demonstrate a strong commitment to delivering services within existing limitations. The study concludes that while the program has been implemented moderately well, its effectiveness depends on strengthening institutional capacity, improving infrastructure, and enhancing coordination among stakeholders. These findings provide important insights for policymakers seeking to improve health policy implementation in rural and remote areas, particularly in developing countries.